2022
DOI: 10.3389/fpubh.2022.843449
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of COVID-19 Vaccine Engagement in Algeria: A Population-Based Study With Systematic Review of Studies From Arab Countries of the MENA Region

Abstract: BackgroundThe Algerian COVID-19 vaccination campaign, which started at the end of January 2021, is marked by a slowly ascending curve despite the deployed resources. To tackle the issue, we assessed the levels and explored determinants of engagement toward the COVID-19 vaccine among the Algerian population.MethodsA nationwide, online-based cross-sectional study was conducted between March 27 and April 30, 2021. A two-stage stratified snowball sampling method was used to include an equivalent number of particip… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
(51 reference statements)
1
4
0
Order By: Relevance
“…Respondents between 30 and 39 were found to be more likely to have positive perceptions of COVID-19 vaccines, these findings align with those of a study conducted in multiple African countries, which found that South Africans in this age group had more favorable perceptions towards COVID-19 vaccines than participants of other age groups [ 42 ]. Moreover, single participants were more likely to have positive vaccine perceptions compared to married participants; a study conducted in Singapore reported nearly the same results [ 43 , 44 ]; however, in their multivariate analysis, they discovered that this association was non-significant [ 45 , 46 ], our analysis found that males were more likely to have a positive perception toward COVID-19, however, there was no significantly impact shaping COVID-19 vaccine perceptions. This deviation could be attributed to shifting gender roles and the shared responsibility of healthcare decision-making between genders, suggesting a lack of apparent gender-based disparities in vaccine hesitancy.…”
Section: Discussionsupporting
confidence: 57%
“…Respondents between 30 and 39 were found to be more likely to have positive perceptions of COVID-19 vaccines, these findings align with those of a study conducted in multiple African countries, which found that South Africans in this age group had more favorable perceptions towards COVID-19 vaccines than participants of other age groups [ 42 ]. Moreover, single participants were more likely to have positive vaccine perceptions compared to married participants; a study conducted in Singapore reported nearly the same results [ 43 , 44 ]; however, in their multivariate analysis, they discovered that this association was non-significant [ 45 , 46 ], our analysis found that males were more likely to have a positive perception toward COVID-19, however, there was no significantly impact shaping COVID-19 vaccine perceptions. This deviation could be attributed to shifting gender roles and the shared responsibility of healthcare decision-making between genders, suggesting a lack of apparent gender-based disparities in vaccine hesitancy.…”
Section: Discussionsupporting
confidence: 57%
“…Reasons for refusing to accept vaccinations are complex, including concerns about side effects of vaccines, perceived need for more clinical studies on the effectiveness and safety of the vaccines, and personal beliefs. 27 Clearly, vaccination is an important preventive measure for symptomatic and severe COVID-19. Vaccine promotion activities should be carried out, and the elderly and other high-risk groups should be encouraged to participate in the vaccination programs.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, there are only a few studies that have evaluated the nutritional risk and the severity of COVID-19 in Chinese patients. 27 Due to different immunization strategies in different countries, the basic health status of the population also varies. It is undoubtedly of great significance to understand the correlation between the nutritional status of Chinese people and the severity of COVID-19 and to carry out nutritional intervention research in the future.…”
Section: Discussionmentioning
confidence: 99%
“…124 For example, studies done during the pandemic showed that one of the causes of vaccine hesitancy and refusal are conspiracy theories created concerning the origin of infection. [127][128][129] Another study conducted in Morocco by Lohiniva et al showed that a part of vaccination hesitancy could be linked to spreading rumors. 130 Hence, the potential increased risk of zoonotic infection transmission during xenotransplant can be partly due to public misinformation in the Arab region, which can be a limitation to necessary vaccination.…”
Section: Prevention Of Xenotransplantation Related Infectionsmentioning
confidence: 99%
“…Many false or misinterpreted information has been spread worldwide, particularly the Arab region 124 . For example, studies done during the pandemic showed that one of the causes of vaccine hesitancy and refusal are conspiracy theories created concerning the origin of infection 127–129 . Another study conducted in Morocco by Lohiniva et al.…”
Section: Selective Diseases Associated With Xenotransplantationmentioning
confidence: 99%